2018
DOI: 10.4314/sajas.v48i1.15
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Zimbabwean Sanga cattle breeds using microsatellite markers

Abstract: Zimbabwe's smallholder land-based livelihoods are dominated by the three local Sanga cattle breeds, namely Mashona, Tuli, and Nkone. A study was carried out to determine genetic diversity and differentiation among conservation populations of these breeds using 16 bovine-specific microsatellite markers. These markers included BM1818, BM1824, BM2113, CSRM60, CSSM66, ETH10, ETH225, ETH3, ILST006, INRA23, RM067, SPS115, TGLA122, TGLA126, TGLA227, and TGLA53. All marker loci contributed to breed differentiation bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
6
21
1
1
Order By: Relevance
“…These average values of PICs were close to those of current study where only five SSRs were used in common (MM12, INRA63, ILSTS011, ILSTS005, and BM1824). Furthermore, Gororo et al [28] found PIC values close to those of actual study with TGLA53 and TGLA 122 using 16 SSR on three breeds from Zimbabwe. The PIC value of INRA37 reported by Harton and Angus [29] on two breeds was lower than that of current founding.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…These average values of PICs were close to those of current study where only five SSRs were used in common (MM12, INRA63, ILSTS011, ILSTS005, and BM1824). Furthermore, Gororo et al [28] found PIC values close to those of actual study with TGLA53 and TGLA 122 using 16 SSR on three breeds from Zimbabwe. The PIC value of INRA37 reported by Harton and Angus [29] on two breeds was lower than that of current founding.…”
Section: Resultssupporting
confidence: 64%
“…Several genetic diversity studies have been conducted on cattle breeds across the world [4][5][6][7]. In Africa, Goudarzi et al [7] studied genetic variability of 201 individuals of the Somba cattle race from Benin and Togo with 33 microsatellite markers whereas, Gororo et al [28] study's was about 50 Sanga cattle race from Zimbabwe using 16 SSRs. In Senegal, N'diaye et al [5] evaluated the genetic diversity of 120 cattle composed of four races from Senegal including N'Dama race using 12 SSR markers.…”
Section: Introductionmentioning
confidence: 99%
“…The observed small genetic differentiation (F ST = 4.8%) is a clear indication of admixture among these ecotypes with clear separation where a Nguni population was subjected to selection linked to the geographic area and specific ethnic groups [17]. In Zimbabwe, Gororo et al [23], using microsatellite markers, observed significant variation between the Mashona, Nkone, and Tuli and concluded that they are distinct breeds. Kotze et al [18] and Bessa et al [19] showed that the Bovines of Tete, Angone, and Landim of Mozambique are genetically related with the former being an admixture between the latter two.…”
Section: Genetic Diversity Of Cattle Breeds In Southern Africamentioning
confidence: 93%
“…South Africa leads in this field owing to advanced sustainable programmes of recording for genetic improvement of cattle breeds [15,17,[20][21][22]. Few studies have been conducted in Zimbabwe [23], Mozambique [18,19], and Tanzania [16].…”
Section: Genetic Diversity Of Cattle Breeds In Southern Africamentioning
confidence: 99%
See 1 more Smart Citation